2022
DOI: 10.3389/fpsyg.2022.847735
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-Based Investigation of Extra-Textual, Connective, and Emphasizing Additions in English-Chinese Conference Interpreting

Abstract: Findings from conference interpreting research in the Chinese context have suggested that interpreters barely produce extra-textual additions in rigidly structured press conferences, and that adding connectives and intensifiers is only required to help the English-speaking audience capture the logic embedded in implicit Chinese interclausal relations. Previous research in the Chinese context has tended to draw data almost exclusively from the Chinese Premier's Press Conference interpreting, which features inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Process-oriented CTIS has witnessed a number of recent key volumes presenting studies primarily based on “behavioral” evidence (e.g., Ferreira and Schwieter, 2014 , 2015 ; Schwieter and Ferreira, 2017 ; Pease and Cheung, 2018 ; Li et al, 2019 , 2022 ; Alves and Jakobsen, 2021 ; Carl, 2021 ; Wu et al, 2021 ; Zhang and Cheung, 2022 ; Chang, 2023 ; Liu X. et al, 2023 ). In contrast, the number of studies in process-oriented CTIS involving “physiological” data relatively pales in comparison.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Process-oriented CTIS has witnessed a number of recent key volumes presenting studies primarily based on “behavioral” evidence (e.g., Ferreira and Schwieter, 2014 , 2015 ; Schwieter and Ferreira, 2017 ; Pease and Cheung, 2018 ; Li et al, 2019 , 2022 ; Alves and Jakobsen, 2021 ; Carl, 2021 ; Wu et al, 2021 ; Zhang and Cheung, 2022 ; Chang, 2023 ; Liu X. et al, 2023 ). In contrast, the number of studies in process-oriented CTIS involving “physiological” data relatively pales in comparison.…”
Section: Research Backgroundmentioning
confidence: 99%
“…However, due to limitations in cognitive resources and time constraints in target language output, omissions may occur. This is particularly evident in the alternating interpreting of longer passages, where the likelihood of omissions and even mistranslations is heightened (e.g., Li R. et al, 2022 ; Song and Matsumi, 2022 ; Zhang and Cheung, 2022 ). Consequently, the target language output during consecutive interpreting may not fully reflect a comprehensive understanding of the source language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past decade, numerous studies utilizing real-world data have confirmed the interpreter's visibility during instances when they were perceived and acknowledged by the communicative participants as effective co-constructors of communication. The majority of these studies centered on the visibility that interpreters themselves initiate, highlighting their active contributions to the discourse in medical (Cirillo, 2012;Zhang and Xu, 2021), legal Vargas-Urpi, 2018, 2019;Pease et al, 2018), educational (Arumí and Vargas-Urpi, 2017;Davitti, 2013), and press conference (Li et al, 2022) settings. On the other hand, only a few studies (Bartłomiejczyk, 2017;Diriker, 2004;Duflou, 2012Duflou, , 2016 have delved into the instances where speakers initiate references to interpreters and/or their output, thereby rendering the interpreters visible.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the aim of this study is to re-examine the interpreter's visibility from an under-researched viewpoint of the speaker's references to interpreters and their output, based on consecutive interpreting in press conferences hosted by the American Institute in Taiwan (AIT), a Chinese interpreting context that has received limited attention (Li et al, 2022). To achieve this research objective, a multimodal conversation analysis methodology was adopted to analyze the data, encompassing both the verbal and non-verbal dimensions of interpreting.…”
Section: Introductionmentioning
confidence: 99%